Mutu Kerupuk Ikan Tenggiri dengan Penggunaan Jenis Pasir yang Berbeda Sebagai Media Penyangraian - Rissinta Mahdalena; Sumardianto Sumardianto; A. Suhaeli Fahmi (Jurnal FishtecH, 2021)
“Kerupuk” are served after the cooking process which can be done by frying in oil, roasting with sand or by grilling. “Kerupuk” cooking process by sand roasting is known to strengthen the taste and reduce the risk of rancidity during storage. The type of sand used in sand roasting generally depends on the availability of sand near the production site. This study is aimed to determine the effect of using different types of sand on the cooking process and to determine the best type of sand that can be used. This experimental laboratory research was carried out with a completely randomized design (CRD). The experimental treatments tested were river sand (S), beach sand (P) and mixed sand (C) where each experimental treatment was tested with three replications. The quality tests of sand-roasted spanish mackerel ‘kerupuk’ were hedonic sensory value, moisture content, efflorescence value, crispness, Scanning Electron Microscopy (SEM) and color test. Nonparametric data were analyzed by Kruskall-Wallis and Mann-Whitney follow-up test. Parametric data from moisture content, efflorescence value, crispness and color were analyzed by ANOVA and Tukey HSD follow-up test. The results of the Tukey HSD test showed that different types of sand produce “kerupuk” with different moisture content and efflorescence, where P produced the lowest water content and the largest efflorescence, while for the crispness of P gives different results from S but both P and S produce the same crispness as C. The best sand that can be used for roasting mackerel “kerupuk” was beach sand with efflorescence value of 72.71 ± 0.92% and crispness of 2.020.15 ± 219.79 gf. The microstructure test results of “kerupuk” roasted in beach sand also showed looser and more porous tissue.